Lexical-semantic analysis of infectious diseases names in English and Serbian language - Jurinjak, Zorana; Lukic, Natasa (PONS - medicinski časopis, 2023)
The issue of this paper is the analysis of infectious disease terms in English and their Serbian equivalents. The author also deals with the influence of the English language on the terminology of infectious diseases in Serbian as a consequence of the contact between these two languages. During the study, professional literature in English, bilingual and monolingual medical and veterinary dictionaries, bilingual collections of papers, abstract books, etymological dictionaries and other works on a similar topic in this area have been used. The analysis is based on 185 English terms and 196 Serbian equivalents for 173 infectious diseases. The processes of the development of terms are established on lexical level and they show great influence of Latin and Greek on both languages. Hybrid loanwords constitute a large section of English corpus, and the most common translation technique is calc. Based on contrastive analysis, the match, mismatch, similarities and differences are found in morphological, syntactic and semantic level. The research shows that a match occurs in over 60% of cases, and that the semantic differences are largely a matter of zero relations. The paper provides the statistical analyses of the research and a series of representative examples in both languages.